Efficiency of butyric acid and inulin in patients with irritable bowels syndrome: results of multicenter study - S. V. Levchenko; I. A. Komissarenko; A. A. Golokhvastova; E. V. Moroz; L. N. Pavlova; L. I. Lesnyak; T. M. Nazarkina; Yu. V. Sergeeva; N. E. Belyanskaya; A. M. Fazylzyanov; L. I. Volodavchik; O. Yu. Mischerina; et al. (Лечащий Врач)
The article presents the results of multicenter post-marketing randomized comparative prospective study of the efficacy of butyric acid and inulin in patients with different types of irritable bowel syndrome in the complex therapy.